Presence of herpesviruses in middle ear fluid of children with otitis media with effusion - Bulut, Yasemin; Karlidag, Turgut; Seyrek, Adnan; Keles, Erol; Toraman, Zulal Asci (Blackwell Publishing, 2007)
Background:Otitis media with effusion (OME) is a disease that frequently occurs in children. Etiopathogenesis of the diseases has not been completely elucidated. There are limited numbers of studies on the presence of herpesviruses in otitis media cases with OME. The present study was undertaken to determine the rate of some herpesviruses in OME cases of children. Methods:A total of 92-middle ear fluids were collected from 51 children. The samples were analyzed using polymerase chain reaction (PCR) for detection of herpesviruses including Herpes simplex virus (HSV), cytomegalovirus (CMV), Varicella zoster virus (VZV), and Epstein-Barr virus (EBV). Results:PCR analysis of the 92 samples showed that genomes of EBV in 12 (13.04%), HSV in seven (7.60%), CMV in five (5.43%), and VZV in three (3.26%) were present. Two of these samples were positive for both HSV and EBV genomes. Therefore, 25 (27.17%) of the samples were determined to be infected with any of the herpesviruses tested. Conclusions: In the present study, herpesviruses were determined at a high rate in middle ear fluids of children with OME. However, the present study is a preliminary study and more extensive studies, especially experimental studies, are required to elucidate the role of herpesviruses in pathogenesis of OME and whether there is a relation between rate of herpesviruses in OME cases, and the reactivation of latent infections.
Keywords: children; herpesviruses; otitis media with effusion